KOMUNITAS GULMA PADA PERKEBUNAN KAKAO (Theobroma cacao) DI DATARAN TINGGI DESA DONGI-DONGI DAN DATARAN RENDAH DESA SIDERA - Yayang Istikana; Wahyu Harso; Ramadanil Pitopang (Biocelebes, 2019)
Different elevation of lands can affect environmental conditions such as light intensity, temperature, and humidity. The environmental conditions will affect the growth and species of weeds. The aim of this study was to compare the diversity and species composition of weed comunities on highland and lowland of cacao plantation. The study was conducted by colecting the weed species from 25 plots with a size of 2 x 2 m. Every plot was placed by purposive sampling. The result showed that there were 26 species of weeds on highland while only 15 species of weeds were found on lowland. Weeds on highland was dominated by Ageratum conyzoides with important value index (IVI) of 62.07% while on lowland was dominated by Euphorbia hirta with IVI of 26.56%. The weeds community has a medium diversity index while the value of Similarity Index (IS) was low (4.87%) between weeds community on highland and lowland. It could be concluded that different environmental condition would affect the number and species of weeds.